Corrosion tests in Hawaiian geothermal fluids - Larsen-Basse, J.; Lam, Kam-Fai (Hawaii Univ., Honolulu (USA). Dept. of Mechanical Engineering, 1984)
Exposure tests were conductd in binary geothermal brine on the island of Hawaii. The steam which flashes from the high pressure, high temperature water as it is brought to ambient pressure contains substantial amounts of Hsub 2S. In the absence of oxygen this steam is only moderately aggressive but in the aerated state it is highly aggressive to carbon steels and copper alloys. The liquid after flasing is intermediately aggressive. The Hawaiian fluid is unique in chemistry and corrosion behavior; its corrosiveness is relatively mild for a geothermal fluid falling close to the Iceland-type resources. 24 refs., 7 figs., 5 tabs.